Sustainability Harmonization of Affordable Housing ( RMB ) Development in Johor With the Waqf Instrument Model - Sukamto, Fifi Anti Mapika Sari; Haji Hashim, Hydzulkifli; Osman, Amirul Faiz (ASR Research India, 2022)
Home is an important home in the beginning of quality and prosperous human life activities. In the face of an era of globalization, every day we are not spared the challenges ahead, hence the home becomes crucial in shaping the next generation. Housing needs should be categorized in the Daruriyyah Maqasid Al Shariah hierarchy. In the context of Hifz An-Nafs collectively carries the meaning of how important it is to meet the basic needs of a human being as a survival. Therefore, with the population of Johor increases to 3.7 million people by 2020, the issue of insufficient housing should be provided properly to ensure that every segment of society can afford to own a house, especially for the B40 and M40 respectively. Among the obstacles that arise include legal problems, financial problems as well as management and administrative problems. The objective of this study is to identify the challenges that exist to developers in developing waqf properties and studying the development system of waqf properties in Malaysia. The results of this study are expected to benefit the parties concerned in compensating for the insufficiency of affordable housing as well as making Johor emulate the concept of Baldatun Toyibbah wa Robbun Ghofur